Hatching rate and survival of larvae of mitre squid Uroteuthis chinensis in aquaculture tank - Dwi Febrianti; Indra Ambalika Syari (Jurusan Akuakultur, Universitas Bangka Belitung, 2016)
Development of squid culture is one effort to prevent the decline of squid population in nature due to continuous capture. Problem faced in the aspect of squid culture is the unavailable information regarding the culture technique of squid in controlled tank. This research was conducted to evaluate the hatching rate of mitre squid Uroteuthis chinensis, and survival of larvae in the controlled tank. The result showed that the hatching rate in culture tank was high, i.e 95.92%, while the survival rate of larvae after hatching was relatively low, only reached 4.25%. The low survival of squid paralarvae was expected because of the administration of single live food which resulted in the low predator response and imbalance of nutrient intake for the development and growth of paralarvae